Human platelet activation by Escherichia coli: roles for FcγRIIA and integrin αIIbβ3. (17th August 2016) - Watson, Callum N.; Kerrigan, Steven W.; Cox, Dermot; Henderson, Ian R.; Watson, Steve P.; Arman, Mònica
Abstract: Gram-negative Escherichia coli cause diseases such as sepsis and hemolytic uremic syndrome in which thrombotic disorders can be found. Direct platelet–bacterium interactions might contribute to some of these conditions; however, mechanisms of human platelet activation by E. coli leading to thrombus formation are poorly understood. While the IgG receptor FcγRIIA has a key role in platelet response to various Gram-positive species, its role in activation to Gram-negative bacteria is poorly defined. This study aimed to investigate the molecular mechanisms of human platelet activation by E. coli, including the potential role of FcγRIIA. Using light-transmission aggregometry, measurements of ATP release and tyrosine-phosphorylation, we investigated the ability of two E. coli clinical isolates to activate platelets in plasma, in the presence or absence of specific receptors and signaling inhibitors. Aggregation assays with washed platelets supplemented with IgGs were performed to evaluate the requirement of this plasma component in activation. We found a critical role for the immune receptor FcγRIIA, αIIbβ3, and Src and Syk tyrosine kinases in platelet activation in response to E. coli . IgG and αIIbβ3 engagement was required for FcγRIIA activation. Moreover, feedback mediators adenosine 5'-diphosphate (ADP) and thromboxane A2 (TxA2 ) were essential for platelet aggregation. These findings suggest that human platelet responses to E. coli isolates are similar to those induced by Gram-positive organisms. Our observations support the existence of a central FcγRIIA-mediated pathway by which human platelets respond to both Gram-negative and Gram-positive bacteria.